2020
DOI: 10.1017/s0022215120002005
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory disorders in coronavirus disease 2019 patients: a systematic literature review

Abstract: Objective Recent scientific literature has widely described a possible major role of smell dysfunction as a specific symptom of coronavirus disease 2019. This systematic review may provide a more holistic approach to current knowledge of the disease. Methods A systematic review was completed using Embase, PubMed and Web of Science databases that considered original articles focused on olfactory evaluation in coronavirus disease 2019 patients, published between March and May 2020, in Engl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 63 publications
(92 reference statements)
1
26
0
Order By: Relevance
“…13,31 Such a wide range may be explained with the heterogeneity of the study protocols. 36 Our results are consistent with those of other studies conducted with hospitalised patients. 19,37 On the contrary, some studies have reported lower or higher olfactory dysfunction or taste impairment.…”
Section: Discussionsupporting
confidence: 93%
“…13,31 Such a wide range may be explained with the heterogeneity of the study protocols. 36 Our results are consistent with those of other studies conducted with hospitalised patients. 19,37 On the contrary, some studies have reported lower or higher olfactory dysfunction or taste impairment.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the overall improving trend, only 40% of patients recovered completely from the OGD at T3. Resolution rate appear to be variable in literature, ranging from 13% [39] to 86% [40] , mainly depending on follow-up duration and OGD evaluation methodology (quantitative vs qualitative) [41] , [42] . In our sample, severity at onset was the most relevant variable influencing complete resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Smell and taste impairment is a well-known sequelae of upper respiratory tract infections. 6 The reported incidence of olfactory dysfunction following upper respiratory tract infection is between 20% and 40%. 1 For typical upper respiratory tract infections, the associated smell and taste impairment mostly occurs as a result of nasal obstruction, which differs from the impairment in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%